Peer education: From enduring problematics to pedagogical potential. (February 2017) - Southgate, Erica; Aggleton, Peter
Background: Peer education is a much-used approach to health education with young people and marginalised groups. Rarely, however, has the concept been interrogated for its meaning and usefulness, despite pleas for the importance of doing so going back several decades. Objectives: Against this background, this paper offers a specifically educational analysis and critique of existing conceptualisations and descriptions of peer education. Design: The paper responds to the challenge of opening up the 'black box' of peer education with respect to teaching and learning, using the pedagogical frameworks offered by Basil Bernstein, critical pedagogy, feminist post-structuralism and Robin Alexander. Results and Conclusion: Findings point to the value of theories of pedagogy as conceptual and analytic lenses through which to interrogate what peer education is (and might be) and to better account for the uneven effectiveness of the approach.